Long-lasting eﬀects of red and blue light exposure on the growth of soil fungi - Vinnikova, Olga I. (Acta Biologica Szegediensis, 2020)
The experimental assessment of inter-species difference in long lasting effects produced in fungi by a brief exposure to the monochromatic light was performed. 24-h cultures grown from 1 mm mycelium fragments of Alternaria alternata, Aspergillus clavatus, Fusarium fujikuroi, Penicillium citrinum and Trichoderma viride were exposed for 30 min to blue light (BL, 450 nm) or red light (RL, 660 nm) and cultured for the next 10 days. Radial growth rate, conidial yield and germination, contents of proteins and phenolsand fungal antibacterial activity were estimated. BL- or RL-exposure did not essentially affect the ﬁnal size of colonies of A. clavatus but delayed the growth of P. citrinum and stimulated it in A. alternata and F. fujikuroi; these changes were more profound after BL, than after RL. In T. viride the BL exposure led to a remarkable delay of growth, whereas the RL signiﬁcantly increased the growth rate. Photo-induced changes in the conidial yield, conidial germination, contents of proteins and phenols also were dependent on the light wavelength and showed strong inter-species heterogeneity. Fungal antibacterial activity in exposed cultures was similar to the unexposed control. The observed effects are indicative targets for future research of possible molecular regulatory mechanisms underlying the photobiology in different fungal taxons.